Competencia entre jurisdicciones y la ineficiencia de los gobiernos locales - Ponzio, Carlos A. (El Colegio de México, A.C., 1998)
In the economics literature there is a standard framework to analyze whether competition among local jurisdictions with mobile populations, ensures efficient public expending. This paper argues that this setting is incomplete, and an alternative model is provided. Though we conclude that, as in the traditional approach, immobile land is a crucial factor preventing the efficiency of local governments, this is not the only reason. In general, we show that governments' efficiency is reached if utility levels do not depend on the size of local populations.